Calidad fisiologica de semilla de soja producida y comercializada por la unidad de semillas de Cooperativa Colonias Unidas - Paraguay - Paniagua, Carlos Roberto Benkenstein (2010)
The present work was based on data of soybean seed analysis from seed lots produced by Colonia Unidas Cooperative - Paraguay, corresponding to the agricultural years (2007 and 2008). The results of 28 varieties were grouped and compared in classes relating to quantity, as well as for germination and vigor. In 2007 they were 331 seed lots while 2008 they were 271. According to the results the following conclusions were taken: a - The quality of soybean seed produced by the Colonia Unidas Cooperative is in a great extent influenced by the climatic conditions during the seed formation, harvesting and storage; b - The adoption of a system of quality control system from harvesting on is essential to diminish seed loss and; c - The decreases of the physiological quality play a role extremely important role on the amount of seed made available to the farmers, as well as the cost of the seed.